Synthesis and Pharmacological Evaluation of α4β2 Nicotinic Ligands with a 3‐Fluoropyrrolidine Nucleus. Issue 6 (16th April 2015) - Tamborini, Lucia; Pinto, Andrea; Ettari, Roberta; Gotti, Cecilia; Fasoli, Francesca; Conti, Paola; De Micheli, Carlo
Abstract Nicotinic acetylcholine receptors (nAChRs) play an important role in many central nervous system disorders such as Alzheimer's and Parkinson's diseases, schizophrenia, and mood disorders. The α4β2 subtype has emerged as an important target for the early diagnosis and amelioration of Alzheimer's disease symptoms. Herein we report a new class of α4β2 receptor ligands characterized by a basic pyrrolidine nucleus, the basicity of which was properly decreased through the insertion of a fluorine atom at the 3‐position, and a pyridine ring carrying at the 3‐position substituents known to positively affect affinity and selectivity toward the α4β2 subtype. Derivatives 3‐(((2S, 4R)‐4‐fluoropyrrolidin‐2‐yl)methoxy)‐5‐(phenylethynyl)pyridine (11) and 3‐((4‐fluorophenyl)ethynyl)‐5‐(((2S, 4R)‐4‐fluoropyrrolidin‐2‐yl)methoxy)pyridine (12) were found to be the most promising ligands identified in this study, showing good affinity and selectivity for the α4β2 subtype and physicochemical properties predictive of a relevant central nervous system penetration.